Arthrobacter agilis and rosy discoloration in "Terme del Foro" (Pompeii, Italy). (May 2018) - Tescari, Marco; Frangipani, Emanuela; Caneva, Giulia; Casanova Municchia, Annalaura; Sodo, Armida; Visca, Paolo
Abstract: Pink patinas and rosy discolorations on stones and mural paintings are often of biological origin, although they are frequently ascribed to chemical causes. This work represents the first report of this kind of biodeterioration in Pompeii, where we found a pink dusty patina in the " Terme del Foro ". Non-invasive sampling was performed to identify the aetiology of the discoloration. Interestingly, the pink pigmented bacterial species Arthrobacter agilis was found associated to the patina, pointing to a role of this bacterial species in rosy discoloration. Both morphology of the isolate and 16S rDNA analysis were consistent with identification as A. agilis. Raman spectroscopy was carried out to compare the pigments from the pink patina with those associated with A. agilis isolates, and the reference strain A. agilis DSM 20550. A spectroscopically identical carotenoid-like pigment was identified in all the three types of sample, arguing for a biological origin of the patina. Observations of pink patina distribution suggest that low-lighting and salinity are likely to play a role in patina development. Graphical abstract: Image 1 Highlights: A pink patina was detected on stone artworks in the archaeological site of Pompeii (Italy). Arthrobacter agilis was isolated as pure culture from the pink patina. The pink colour was consistent with carotenoid pigments produced by A. agilis . An association between stone colonization by A. agilis and pink discoloration is suggested.